Atractylodin Attenuates Dextran Sulfate Sodium-Induced Colitis by Alleviating Gut Microbiota Dysbiosis and Inhibiting Inflammatory Response Through the MAPK Pathway - Qu, Linghang; Lin, Xiong; Liu, Chunlian; Ke, Chang; Zhou, Zhongshi; Xu, Kang; Cao, Guosheng; Liu, Yanju (Frontiers in Pharmacology, 2021)
In this study, we investigated the therapeutic effects and mechanism of atractylodin(ATL) on dextran sulfate sodium (DSS)-induced ulcerative colitis in mice. We found that atractylodin could significantly reverse the effects of DSS-induced ulcerative colitis, such as weight loss, disease activity index score; shorten the colon length, and reverse the pathological changes in the colon of mice. Atractylodin could inhibit the activation of colonic macrophages by inhibiting the MAPK pathway and alleviate intestinal inflammation in the mouse model of ulcerative colitis. Moreover, atractylodin could protect the intestinal barrier by inhibiting the decrease of the tight junction proteins, ZO-1, occludin, and MUC2. Additionally, atractylodin could decrease the abundance of harmful bacteria and increase that of beneficial bacteria in the intestinal tract of mice, consequently improving the intestinal microecology. In an LPS-induced macrophage model, atractylodin could inhibit the MAPK pathway and expression of the inflammatory factors of macrophages. Atractylodin could also inhibit the production of lactate, which is the end product of glycolysis; inhibit the activity of GAPDH, which is an important rate-limiting enzyme in glycolysis; inhibit the malonylation of GAPDH, and, thus, inhibit the translation of TNF-α. Therefore, this study is the first to highlight the potential of atractylodin in the treatment of ulcerative colitis and reveal its possible mechanism.